Screening of SIRT2 inhibitors from natural product databases using computer-aided drug design and molecular dynamics simulation - Tianyi Liu; Hongli Yin; Xue Dong; Qingyang Hu; Xuejiao Hu; Wenxin Yan; Huanhuan Wang; Zhong Li (Brazilian Journal of Pharmaceutical Sciences)
Abstract This study is committed to searching for inhibitors of deacetylase SIRT2 within the natural product database via computer-aided drug design techniques. A comprehensive computer-aided drug design platform has been successfully established by integrating various techniques such as drug-likeness screening, pharmacokinetic prediction, molecular docking, and molecular dynamics simulation. The Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (YaTCM) has been thoroughly explored to identify SIRT2 inhibitors, and the discovered compounds have been validated using molecular dynamics simulation. Through the computer-aided drug design method, five compounds capable of binding to SIRT2 have been successfully screened out from 47,696 natural product compounds derived from 6,220 herbs in the YaTCM database. Molecular dynamics simulation reveals that Artonin E and Paleatin B can form stable receptor-ligand complexes in the active pocket of SIRT2 inhibitors. Based on computer-aided drug design and virtual screening and verification techniques, Artonin E and Paleatin B have been identified as inhibitors of SIRT2, which is a key therapeutic target for the treatment of neuroblastoma. Applying computer aided drug design techniques to identify potential drug molecules from natural products holds profound significance for drug research.